Class attendance management system using face recognition - Abdul Rhman Salim, Omar; Olanrewaju, Rashidah Funke; Balogun, Wasiu Adebayo (Institute of Electrical and Electronics Engineers Inc., 2018)
We are living in a world where everything is automated and linked online. The internet of things, image processing, and machine learning are evolving day by day. Many systems have been completely changed due to this evolve to achieve more accurate results. The attendance system is a typicalexample of this transition, starting from the traditional signature on a paper sheet to face recognition. This paper proposes a method of developing a comprehensive embedded class attendance systemusing facial recognition with controlling the door access. The system is based on Raspberry Pi thatruns Raspbian (Linux) Operating System installed on micro SD card. The Raspberry Pi Camera, as well as a 5-inch screen, are connected to the Raspberry Pi. By facing the camera, the camera will capture the image then pass it to the Raspberry Pi which is programmed to handle the face recognition by implementing the Local Binary Patterns algorithm LBPs. If the student's input image matches withthetrained dataset image the prototype door will open using Servo Motor, then the attendance results will be stored in the MySQL database. The database is connected to Attendance Management Syste(AMS) web server, which makes the attendance results reachable to any online connected web browser.The system has 95{% accuracy with the dataset of 11 person images.